Effect of pH on Hydroponically Grown Bush Beans (phaseolus vulgaris) - Hopkinson, Sampson; Harris, Megan (International Journal of Environment, Agriculture and Biotechnology, 2019)
Numerous environmental factors can influence the viability of plants. Several studies have shown that acidic and basic pHs have a noticeable effect on different types of plants when grown directly in soils. However not too many studies have been done on hydroponically grown plants with respect to pH. This study was conducted at the Botany laboratory and Green house at Alabama A & M University with bush beans. Five nutrient solutions with pH values ranging from 5 - 9 were used. Observations on plant height and number of leaves were done for six weeks after nutrient solutions with the different pH values were introduced to the plants 7 days after the seed germinated. Plants grown in nutrient solutions with high alkalinity levels (8 & 9) were significantly shorter compared to those grown in nutrient solutions with pH 5, 6 and 7. Leaf number and size strongly correlated in a manner expected with plant height, plants in high alkalinity nutrient solutions had fewer and smaller leaves. Plants grown in neutral or near neutral nutrient solutions appear healthier with green leaves and strong stems.